2016
DOI: 10.1021/acs.jnatprod.6b00484
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucosidase and α-Amylase Inhibitors from Arcytophyllum thymifolium

Abstract: Three new coumarins (1-3), a prenylated flavanone (4), and two iridoids (5 and 6), together with 17 known secondary metabolites, were isolated from the aerial parts of Arcytophyllum thymifolium. The structures of the new compounds were elucidated on the basis of their spectroscopic data. The potential hypoglycemic properties of the new and known compounds were evaluated by measuring their α-amylase and α-glucosidase inhibitory effects. The iridoid asperulosidic acid (15) and the flavonoid rhamnetin (13) showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 44 publications
(80 reference statements)
2
45
0
Order By: Relevance
“…Hypoglycemic activity of CE and AF was tested by evaluating their inhibitory activity against α-glucosidase and α-amylase, two of the main enzymes involved in postprandial hyperglycemia modulation [41]. AF represents 28% (g/g dry CE) and this recovery agreed with the range of data reported in literature by Lee et al [5] and Lao et al [1] for other purple corn cob varieties.…”
Section: Evaluation Of Hypoglycemic Activitysupporting
confidence: 82%
See 1 more Smart Citation
“…Hypoglycemic activity of CE and AF was tested by evaluating their inhibitory activity against α-glucosidase and α-amylase, two of the main enzymes involved in postprandial hyperglycemia modulation [41]. AF represents 28% (g/g dry CE) and this recovery agreed with the range of data reported in literature by Lee et al [5] and Lao et al [1] for other purple corn cob varieties.…”
Section: Evaluation Of Hypoglycemic Activitysupporting
confidence: 82%
“…The α-amylase inhibition assay was performed following the method reported by Milella et al [41] with some modifications. Briefly, 500 µL of Type VI-B porcine pancreatic α-amylase (0.5 mg/mL in 100 mM sodium phosphate buffer, containing 6.7 mM sodium chloride, pH 6.7-PBS) were preincubated with 500 µL of each sample (CE or AF) in test tubes at 37 • C for 10 min.…”
Section: α-Amylase Inhibitory Activitymentioning
confidence: 99%
“…In this study, it was also observed that the concentration of flavonoids of A. indica was significantly lower when compared with that of P. nigrescens at P<0.05. As natural antioxidants, flavonoids play an important role in scavenging free radicals and preventing degenerative diseases such as cardiovascular diseases [58,59,60]. However, they are also involved in the antiproliferation of carcinogenic cells, in cell cycle regulation and in the induction of apoptosis [61,62,63].…”
Section: Resultsmentioning
confidence: 99%
“…Optical rotations were measured on an Atago AP-300 digital polarimeter equipped with a sodium lamp (589 nm) and a 1-dm microcell. NMR experiments were recorded at 300 K in CD 3 OD on a Bruker DRX-600 spectrometer (Bruker BioSpin GmBH) equipped with a Bruker 5 mm TCI CryoProbe as reported previously [26]. HRESIMS were acquired in the positive ion mode on a LTQ Orbitrap XL mass spectrometer (Thermo Fisher Scientific).…”
Section: General Experimental Proceduresmentioning
confidence: 99%